Multifocal tuberculosis verrucosa cutis - Jiby Rajan; Ashok Thomas Mathai; P.V.S Prasad; P K Kaviarasan (Wolters Kluwer Medknow Publications, 2011)
Tuberculosis has been a well-known affliction of human kind, since antiquity. Cutaneous tuberculosis constitutes only a small proportion of extra pulmonary tuberculosis and multifocal involvement of cutaneous tuberculosis is an even rarer manifestation. We report one such case of multifocal tuberculosis verrucosa cutis in a 17-year old male patient in the absence of any primary tuberculous focus.